Constraints on Gamma-Ray Burst Models from GRB 221009A: GeV Gamma Rays versus High-energy Neutrinos - Ruo-Yu Liu; Hai-Ming Zhang; Xiang-Yu Wang (The Astrophysical Journal Letters, 2023)
Gamma-ray bursts (GRBs) are generally believed to be efficient particle accelerators. In the presence of energetic protons in a GRB jet, interactions between these protons and the intense radiation field of the GRB are supposed to induce an electromagnetic cascade. Electrons/positrons generated in the cascade will produce an additional spectrum of a robust feature, which is in the form of a power-law distribution up to a GeV regime with an index of ≲2. We suggest that measurements of the Fermi Large Area Telescope at the GeV band can provide independent constraints on the key GRB model parameters such as the dissipation radius, the jet’s bulk Lorentz factor, and the baryon loading factor. Taking GRB 221009A, the brightest GRB ever detected, as an example, we show that the constraints from GeV gamma-ray emission may be more stringent than that from the neutrino observation, providing us with deep insight into the origin of GRBs.